Magnetic Properties of Tetragonal SmFe12−xMox Alloys in Bulk and Melt‐Spun Ribbons. Issue 15 (4th August 2022) - Rodríguez-Crespo, Bosco; Garcia-Franco, Andrés; Rosero-Romo, James Janderson; Echevarria-Bonet, Cristina; Porro, Jose Maria; Saiz, Paula G.; Salazar, Daniel
Abstract : Critical Raw Materials Total or partial substitution of critical raw materials, such as rare‐earth elements in permanent magnets, drives the implementation of greener technologies for the development of electric generators and motors. Magnets play a key role in the performance of devices used in wind turbines, electronic mobility, aerospace technology, robotics and high‐efficiency data storage. More information can be found in article number 2100725 by Daniel Salazar and co‐workers.